EFFECTIVENESS OF MULTIPLE REPRESENTATION-BASED SCAFFHOLDING IN CHEMISTRY LEARNING: A STUDY ON 3T STUDENTS WITH LOW NUMERACY ABILITY - Damayanti, Yosephine Debbie; Wulanningtyas, Melania Eva (International Journal of Active Learning, 2025)
This study aims to analyze the effectiveness of scaffolding-based learning with multiple representations in improving students' understanding of atomic structure and electron configuration. The subjects of the study consisted of 42 students from the 3T area, who were divided into an experimental group and a control group. The experimental group received learning with scaffolding based on multiple representations, while the control group received conventional learning. The results showed that there was a significant increase in conceptual understanding in the experimental group, with an average pretest score of 45.2 and a posttest score of 78.5. In addition, the scaffolding technique based on multiple representations was proven effective in reducing students' misconceptions about atomic structure and electron configuration, as well as increasing their learning motivation. Therefore, this learning strategy is recommended to be widely applied in chemistry learning, especially for students in the 3T area who have limited access to learning resources and low numeracy skills.